The SURVEY OF PUBLIC KNOWLEDGE ABOUT NEW NORMAL BEHAVIOR AFTER COVID-19 : SURVEY OF PUBLIC KNOWLEDGE ABOUT NEW NORMAL BEHAVIOR AFTER COVID-19 - Eppy Setiyowati; Ni Njoman Juliasih; Renny Mareta Sari (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Introduction Coronavirus virus disease pandemic 2019 (Covid-19) has not shown improved health conditions, it is necessary to conduct an in-depth survey of public knowledge in carrying out healthy living behaviors after the Covid-19 pandemic. Clean and healthy living behavior is one of the efforts in maintaining personal and environmental hygiene. The purpose of the study was to conduct an analysis of public knowledge about clean and healthy living behaviors after the covid-19 pandemic. Method Design used in qualitative research with explanatory survey approach. The technique of sampling snowballs over the internet online, an anonymous online instrument was developed using google form. Questionnaire links were sent via email, WhatsApp, and other social networks through researchers. The instrument packaged in structured questioner form (included as an additional file) consists of questions covering several fields: (1) sociodemographic data (age, gender and level of education), (2) New normal behavior habits include wearing a mask, washing hands with soap or hand sanitizer, social distancing, Do not a crowd with many people, keep the environment around the residence always clean and healthy, packaged in google form. Data recapitulation and processing are carried out with the help of IT, then qualitative analysis. Research Results In this study, we conducted explorations related to sociodemographic, environmental hygiene around the place, healthy behavior habits including, wearing masks, hand washing, social distancing, availability of facilities for hand washing with hand sanitizer or hand washing with running water. The results showed that the community has carried out new normal behavior with awareness without any compulsion from anywhere. Thus new normal behavior includes, wearing masks, washing hands with running water or hand sanitizer and social distancing has become a new habit in order to break the chain of spread of 'covid 19. Conclusion With a better understanding of the new normal behavior, people are able to break the indirect chain of transmission of COVID-19 in everyday life